THE EFFECT OF PRODUCT QUALITY AND SERVICE QUALITY ON CUSTOMER SATISFACTION AT ALFAMIDI RINGROAD STORE 3 - Manurung, Lambok; Etty Harya Ningsi; Slamet Widodo (Jurnal Ekonomi, 2022)
This study is examining the effect of product quality (X1) and service quality (X2) on the customer satisfaction of ALFAMIDI shop ring-road 3 with a total of 90 respondents in this study conducted in 2021. This analysis includes classical assumption test, multiple regression analysis, hypothesis testing through t-test and F test, and analysis of the coefficient of determination (R2). The results of the analysis using the t-test can be seen that the independent variable namely product quality (X1) has a positive but not significant effect partially on the dependent variable, namely customer satisfaction (Y) while it is known that the independent variable namely service quality (X2) has a positive but not significant effect partially on the dependent variable, namely customer satisfaction (Y). The results of the analysis using the F test can be seen that the two independent variables, namely product quality (X1) and service quality (X2) together have a positive but not significant effect on the dependent variable namely customer satisfaction (Y). The results of the analysis using the coefficient of determination are known that 01.2% of employee performance can be obtained and explained by product quality (X1) and service quality (X2). While the remaining 98.8% is explained by other variables not included in this study.